Unknown [videorecording (DVD)] - Ottman, John; Rudd, Alexander (Warner Home Video, 2011)
Dr. Martin Harris awakens after a car accident in Berlin to discover that his wife suddenly doesn't recognize him and another man has assumed his identity. Ignored by disbelieving authorities and hunted by mysterious assassins, he finds himself alone, tired, and on the run. Aided by an unlikely ally, Harris plunges into a deadly mystery, forcing him to question his sanity, his identity, and just how far he's willing to go to uncover the truth.